Near-Infrared Light Regulation of Capture and Release of ctDNA Platforms Based on the DNA Assembly System - Gong, Chaihong; Mao, Xiaowei; Wang, Zhe; Luo, Zhang; Liu, Zhifan; Ben, Yali; Zhang, Weiying; Guo, Zhenzhong (Frontiers in Bioengineering and Biotechnology, 2022)
Despite recent progresses, a challenge remains how to gently releasing and recovering viable ctDNA captured on DNA probe-based devices. Here, a reusable detector was successfully developed for the highly sensitive and selective capture and release of ctDNA using UCNPs@SiO2-Azo/CD-probe. Biocompatible NIR light is used to excite UCNPs and converted into local UV light. Continuous irradiation induces a rapid release of entire ctDNA-probe-CD complex from the functionalized surface via the trans−cis isomerization of azo units, without disrupting ctDNA-structure receptor. Specifically, these composite chips allow reloading DNA probe for further ctDNA capture and the repeated application of these chip has no obvious influence on their efficiency. The results of this study demonstrate the potential of this platform for the quantitative detection of ctDNA and for the individualized analysis of cancer’s patients.